CONTENT OF URANIUM ISOTOPES IN THE GROUNDWATER SUPPLIES USED FOR POPULATION OF LENINGRAD REGION AND ST-PETERSBURG - M. V. Kaduka; L. N. Basalaeva; T. A. Bekyasheva; S. A. Ivanov; N. V. Salazkina; V. V. Stupina; A. N. Kaduka (Радиационная гигиена)
The aim of the study was to obtain 234U and 238U specific activity in the water of groundwater supplies of Leningrad region and St-Petersburg and to estimate the possibility of their using from the point of view of radiation and chemical toxicity of the main dose-forming uranium isotopes usually containing in the underground waters. The study was focused on the water of functioning and exploratory groundwater supplies concerning the safety of water consumption taken into account radiation and chemical index. Data on the levels of natural uranium isotopes specific activity in the sources under investigation was obtained using radiochemical analysis with the subsequent alpha-spectrometric measurement of the counting samples. 58 samples of natural groundwater were analyzed during the period from February of 2011 till the May of 2017. The volume of the native water samples was from 10 l to 30 l, measuring time for each counting sample was 6 – 12 hours, which allowed measuring the radionuclides specific activity value at the level of 0.0002 Bq/kg. The values of 238U specific activity varied within 0.0002 Bq/kg – 0.06 Bq/kg, the average value was 0.007 Bq/kg. The values of 234U specific activity varied within 0.0006 Bq/kg – 0.111 Bq/kg, the average value was 0.013 Bq/kg. The average value of the specific activities ratio 234U/238U was 2.12 and the range of this value was 1.00 – 8.00. The results of carried out investigations demonstrates that the specific activity values of uranium isotopes could differ more then by an order of magnitude even in the borders of same aquifer of a small settlement. 238U specific activity value does not exceed 0.02 Bq/kg and 234U specific activity value does not exceed 0.04 Bq/kg for the vast majority of analyzed sample. The value of the ratio 234U/238U was 1.00 – 4.00 for 98.3% of analyzed sample. It is possible to conclude with a high probability that the water from the groundwater supplies of Leningrad region and St-Petersburg is safe for consumption by population concerning 234U and 238U content as from the point of view of radiological factor, so from the point of view of chemical toxicity.